Professor Faustino Esposel: Neurology, football and spiritualism - Novis, Luiz Eduardo; Maranhão, Péricles Andrade, Filho; Pires, Maria Elisa Paiva; Spitz, Mariana; Teive, Hélio Afonso Ghizoni (Arquivos de Neuro-Psiquiatria, 2021)
Faustino Monteiro Esposel was a renowned neurologist from Rio de Janeiro, born on October 24, 1888. Together with his mentor, Professor Antônio Austregésilo Rodrigues Lima - the founder of modern Brazilian Neurology -, Professor Esposel described one of the rival signs of the Babinski sign, known as the Austregésilo-Esposel sign, in a study published in the renowned journal L'Encéphale in 1912. This article aims to summarize the life story of this illustrious neurologist as well as to highlight his achievements “beyond medicine”.
Keywords: History of Neurology; Neurology; Semiology; Babinski sign; Austregésilo-Esposel sign